Phosphorylation of ribosomal protein S6 differentially affects mRNA translation based on ORF length - Bohlen, Jonathan; Roiuk, Mykola; Teleman, Aurelio A. (Nucleic acids research, 2021)
Phosphorylation of Ribosomal Protein S6 (RPS6) was the first post-translational modification of the ribosome to be identified and is a commonly-used readout for mTORC1 activity. Although the cellular and organismal functions of RPS6 phosphorylation are known, the molecular consequences of RPS6 phosphorylation on translation are less well understood. Here we use selective ribosome footprinting to analyze the location of ribosomes containing phosphorylated RPS6 on endogenous mRNAs in cells. We find that RPS6 becomes progressively dephosphorylated on ribosomes as they translate an mRNA. As a consequence, average RPS6 phosphorylation is higher on mRNAs with short coding sequences (CDSs) compared to mRNAs with long CDSs. We test whether RPS6 phosphorylation differentially affects mRNA translation based on CDS length by genetic removal of RPS6 phosphorylation. We find that RPS6 phosphorylation promotes translation of mRNAs with short CDSs more strongly than mRNAs with long CDSs. Interestingly, RPS6 phosphorylation does not promote translation of mRNAs with 5′ TOP motifs despite their short CDS lengths, suggesting they are translated via a different mode. In sum this provides a dynamic view of RPS6 phosphorylation on ribosomes as they translate mRNAs and the functional consequence on translation.
Gesehen am 10.05.2022